Variability of thermohaline properties in Pearl Lagoon, Nicaragua (ESP) - Brenes, Carlos L. (2008)
Several hydrographic surveys were carried out in Pearl Lagoon, Nicaragua between april 1995 and december 1997 under the DIPAL (Proyecto para el Desarrollo Integral de la Pesca Artesanal en la Región Autónoma del Atlántico Sur) project. Surface temperature, salinity, dissolved oxygen and turbidity have been measured in 88 hydrographic campaigns. The annual cycle shows maximum and minimum temperatures in May (29.4 °C) and December (25.6 °C) respectively, maximum salinity (25.6 °C) in April, one month before the thermal peak, and minimum salinities (2‰) between July and August, when the annual precipitation index attains its seasonal maximum in the study area. In the case of dissolved O2 the maximum values of oxygen saturation were observed between March and May (90%), when the water turbidity in the lagoon is at its lowest and freshwater contributions from the rivers attains its minimum value. During the rainy season, in the second half of the year, there is an important decrease in oxygen contents, mainly as a consequence of the degradation of organic matter of riverine origin.